Healthcare research and development (R&D) as reflected in digital news: Analysis from Kenya, Nigeria, and South Africa - Emily Ndulue; Sandra Roberts; Praise Abraham (The African Journal of Information and Communication)
This study used a new open-source repository of African news media to study coverage of healthcare research and development (R&D) in the news ecosystems of Kenya, Nigeria, and South Africa. A corpus of more than 5 million potentially relevant news articles was filtered through refined queries, ultimately yielding 2,917 highly topically relevant articles from 377 publications. These were analysed using both computational natural language processing (NLP) and manual qualitative analysis. The study revealed the following: the types of healthcare developments that were making news in each of the three countries (e.g., new medical technologies, activities of high-profile individuals in the health space, and health sector-building events); the diseases and conditions being prioritised (e.g., HIV/AIDS and mental health); the key stakeholders in the sector (e.g., government officials and funding organisations); and the media narratives around the impact of healthcare R&D (including emphasis on digital health). The study illustrates the value of using large news datasets to gain a deeper understanding of developments and discourse around rapidly evolving topics of high social importance, such as healthcare.